A robust SNP-haplotype assay for Bct gene region conferring resistance to beet curly top virus in common bean (Phaseolus vulgaris L.) - Soler-Garzón, Alvaro; Goldoff, Deidrah; Thornton, Alyson; Swisher Grimm, Kylie D.; Hart, John P.; Song, Qijian; Strausbaugh, Carl A.; Miklas, Phillip N. (Frontiers in Plant Science, 2023)
Beet curly top virus (BCTV), which is synonymous with Curly Top Virus (CTV), causes significant yield loss in common bean (snap and dry beans) cultivars and several other important crops. Common bean cultivars have been found to be resistant to CTV, but screening for resistance is challenging due to the cyclical nature of epidemics and spotty feeding by the leafhopper that vectors the virus. We used a SNP dataset for the Snap Bean Association Panel (SnAP) agro-inoculated with CTV-Logan (CA/Logan) strain to locate the Bct gene region to a 1.7 Mb interval on chromosome Pv07 using Genome-wide association study (GWAS) analysis. Recombinant lines from the SnAP were used to further narrow the Bct region to a 58.0 Kb interval. A missense SNP (S07_2970381) in candidate gene Phvul.007G036300 Exonuclease V (EXO5) was identified as the most likely causal mutation, and it was the most significant SNP detected by GWAS in a Dry Bean Population (DBP) naturally infected by the CTV-Worland (Wor) strain. Tm-shift assay markers developed for SNP S07_2970381 and two linked SNPs, S07_2970276 and S07_2966197, were useful for tracking different origins of the Bct EXO5 candidate gene resistance to CTV in common bean. The three SNPs identified four haplotypes, with haplotype 3-1 (Haplo3-1) of Middle American origin associated with the highest levels of CTV resistance. This SNP-haplotype assay will enable breeders to track resistance sources and to develop cultivars with better CTV resistance.